2021
DOI: 10.1111/isj.12355
|View full text |Cite
|
Sign up to set email alerts
|

A tale of two frames: Exploring the role of framing in the use discontinuance of volitionally adopted technology

Abstract: The discontinuance of volitional IS (i.e., information systems adopted, used and discontinued at will) has recently attracted remarkable attention from academics and practitioners alike. However, most research to date has been ahistorical. Ignoring the temporal progression can be problematic when the phenomenon under investigation is dynamic and evolving. To balance this, we adopt a stage modelling approach to understand the process ending with the technology use being discontinued by users of a popular crowds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 133 publications
(300 reference statements)
0
5
0
Order By: Relevance
“…Therefore, it is essential to train users to use new technology and inform them about the usefulness of using a new will to continue using it. Many industrial reports mentioned that there is a high rate of discontinuance of using technology after using it such as mobile applications and new emerging technology, after using it for a short time ([ 65 , [66] , [67] , [68] ]), which needs more studies to find out the rationale of discontinuance of using new technology.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is essential to train users to use new technology and inform them about the usefulness of using a new will to continue using it. Many industrial reports mentioned that there is a high rate of discontinuance of using technology after using it such as mobile applications and new emerging technology, after using it for a short time ([ 65 , [66] , [67] , [68] ]), which needs more studies to find out the rationale of discontinuance of using new technology.…”
Section: Discussionmentioning
confidence: 99%
“…In the whole lifecycle of technology, frames that people refer to have a robust association with their final choices on accepting or refusing this technology [ 43 ]. In their study of discontinuance of volitional information system (IS), they identified two frames – the hedonic frame and the gain frame.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to self‐determination theory, both hedonic and instrumental rationales determine an individual's attitudes and behaviour (Chiu et al, 2014; Chu et al, 2015; Soliman & Tuunainen, 2021). Drawing on the instrumental–hedonic framework, gamer orientation can be classified into instrumental and hedonic orientations.…”
Section: Theoretical Frameworkmentioning
confidence: 99%